Dietary practices amongs students of Universiti Teknologi MARA Cawangan Kelantan /Wan Nuur Fazliza Wan Zakaria - Wan Zakaria, Wan Nuur Fazliza; Mohd Tahir, Ain Nazira; Baharudeen, Nur'Atiqah; Zulkifli, Nur Zulharni Aisha (2021)
: Healthy eating practices has become difficult to be observed among Malaysians due to changes in their present lifestyles. Recognising the importance of promoting health and preventing diseases during the period of transition from adolescence to adult life, the current study aims to firstly find out university students' meal consumption patterns before determining food preferences of the students. It also seeks the difference between accommodation status and students' body mass index (BMI). The data of this study were gathered from 118 respondents from UiTM Cawangan Kelantan. The instrument used was a set of questionnaires adapted from Yun, Ahmad and Quee (2018). The data were analysed using Statistical Package of Social Sciences (SPSS) 23.0 via descriptive analysis, while to identify the difference between accommodation status and students' BMI, the statistical analysis included an independent t-test. It was revealed that most of the students ate meals regularly on a daily basis but were inclined to skip meals, mainly breakfast. The students also preferred to eat foods that were easy to consume, and they opted for foods at cheaper prices over healthy and nutritious ones. The study also found that there was a significant difference between accommodation status and the students' BMI. The results indicate that the students did not implement healthy dietary practices in their lives. Apparently, university students need to be assisted so as to become responsible adults who can develop healthy dietary practices.